Application of instant messaging software in the follow‐up of patients using peritoneal dialysis, a randomised controlled trial. Issue 15 (6th June 2018) - Cao, Fang; Li, Lanfei; Lin, Miao; Lin, Qinyu; Ruan, Yiping; Hong, Fuyuan
Abstract : Aims and objectives: This study aims to investigate the application value of Internet‐based instant messaging software in the follow‐up of patients using peritoneal dialysis. Background: Peritoneal dialysis is an effective renal replacement treatment for end‐stage renal disease. The clinical usefulness of Internet‐based instant messaging software in the follow‐up of peritoneal dialysis patients, including the incidence of peritonitis and exit‐site infection, the levels of albumin and electrolytes and the degree of patients' satisfaction, remains unknown. Design: Between January 2009–April 2016, a total of 160 patients underwent continuous peritoneal dialysis in the Department of Nephrology, Fujian Provincial Hospital were invited to participate voluntarily in this study. The patients were randomly assigned to the instant messenger (QQ) follow‐up group ( n = 80) and the traditional follow‐up group ( n = 80). The differences in death, hospitalisation, peritonitis, exit‐site infection, and patients' satisfaction were investigated during 1 year of follow‐up. The mean follow‐up duration is 11.4 ± 1.5 months. Results: Compared with the patients in the traditional follow‐up group, patients in the QQ follow‐up group showed higher levels of serum albumin ( p = .009) and haemoglobin ( p = .009), lower levels of phosphorus ( p < .001) and calcium‐phosphorus product ( p = .001), and better degree of satisfaction ( p < .001). Relevance to clinical practice: Internet‐based follow‐up by instant messaging software appears to be a feasible and acceptable method of delivering peritoneal dialysis treatment for patients with end‐stage renal disease.